Contribution of tourism to the OECS economies. - SAMUEL, Wendell A. (1991)
Analyses and compares tourism statistics of the 1970s and 1980s for the OECS countries, and looks at the limitations of these statistics. Presents a framework for estimating the contribution of tourism to the economies of the OECS.